2019
DOI: 10.1002/slct.201901041
|View full text |Cite
|
Sign up to set email alerts
|

TiO2/rGO/CuS Nanocomposites for Efficient Photocatalytic Degradation of Rhodamine‐B Dye

Abstract: In this work, a simple two step synthesis of Titanium dioxide / Reduced graphene oxide / Copper sulfide (TiO2/rGO/CuS) and its improved photocatalytic activity is reported. TiO2/rGO is prepared by electrochemical anodization of Ti metal in NaCl‐graphene oxide solution as an electrolyte. Later CuS is incorporated to TiO2/rGO to form the composite TiO2/rGO/CuS by chemical precipitation at room temperature. The optical properties, phase and morphology of the material is characterized by UV‐visible spectroscopy, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…When compared to pure TiO 2 or TiO 2 /rGO, TiO 2 /rGO/CuS exhibited increased photocatalytic activity attributed to the interfaced rGO and CuS's broad optical absorption spectrum resulting in efficient charge separation. 102 Similar, results were obtained by Ojha et al 104 in the photocatalytic activity of the CdS@TiO 2 /rGO nanocomposite. 104,105 There are several major obstacles to overcome while investigating the use of TiO 2 /GO photocatalysts in the wastewater treatment process, including catalytic stability, passivation, and limited up scalability of a method based on a catalyst in suspension.…”
Section: Recent Research Carried Out In Wastewater Treatment Through ...supporting
confidence: 79%
See 1 more Smart Citation
“…When compared to pure TiO 2 or TiO 2 /rGO, TiO 2 /rGO/CuS exhibited increased photocatalytic activity attributed to the interfaced rGO and CuS's broad optical absorption spectrum resulting in efficient charge separation. 102 Similar, results were obtained by Ojha et al 104 in the photocatalytic activity of the CdS@TiO 2 /rGO nanocomposite. 104,105 There are several major obstacles to overcome while investigating the use of TiO 2 /GO photocatalysts in the wastewater treatment process, including catalytic stability, passivation, and limited up scalability of a method based on a catalyst in suspension.…”
Section: Recent Research Carried Out In Wastewater Treatment Through ...supporting
confidence: 79%
“…(g) Energy band diagram of TiO 2 /rGO/CuS and the degradation mechanism of Rhodamine-B dye. Reprinted with permission from ref . Copyright 2019, Wiley (no changes).…”
Section: Recent Research Carried Out In Wastewater Treatment Through ...mentioning
confidence: 99%
“…Shows the Raman spectra of pure Bi 2 Zr 2 O 7 pyrochlore materials in which six active modes are appeared in region between 200 to 700 cm À1 , and the modes at 253, 323, 467, 513, 569 and 650 cm À1 are signifying that the prepared samples belongs to pyrochlore phase. The observed bands are related to F 2g (4) at (253, 323, 564 and 650 cm À1 ) E g (1) at 467 cm À1 , and A 1g (1) at 513 cm À1 vibration respectively. 18,30,31 The broad peak resulting from the combination of rst order and second order scattering due to the electron-phonon coupling effects.…”
Section: Raman Spectra Analysismentioning
confidence: 85%
“…These organic molecules have been considered as harmful to the environment and human beings. [1][2][3] In earlier studies, it is reported that 15% of synthetic textile and pharma wastes are abruptly mixed with the main water streams. Colorful dyes and pharmaceutical organic solutions in the water stream will prevent the penetration of light, which totally disturbs the biological processes in the aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the (rGO/CuS-7) composite exhibited the highest efficiency (97.6%) for degrading MG in sunlight for 90 min and this photocatalyst could also be recycled for five times without any significant loss in its activity. Titanium dioxide/ reduced graphene oxide/copper sulfide (TiO 2 /rGO/CuS) composite was synthesized (Gunnagol and Rabinal, 2019). They observed its photocatalytic activity in degradation of rhodamine-B under ultraviolet as well as visible light exposures.…”
Section: Introductionmentioning
confidence: 99%